(untitled) (Discussion Papers, 2012)
The present volume introduces the East-Central European achievements of regional development policy. Besides the analyses of the territorial transformation processes of the transformation period the studies draw a comprehensive picture of the economic and political factors influencing the organisation of the territorial medium tier - the region - as well as the characteristics of the objectives, means and institutional system of regional development introducing significantly different approaches of certain countries on the regional policy tasks of the state, the future of the autonomous political action space of the regions. While in Eastern Europe even the application of the traditional state regional policy causes vital debates, in Western Europe and the United States already a different, post-modern type of regional political praxis is becoming generally applied. This new practice is introduced by the last two studies of the volume. This volume is an overture of the research programme, which was launched by the Centre for Regional Studies in order to investigate the East-Central European transformation.